2020
DOI: 10.1097/corr.0000000000001424
|View full text |Cite
|
Sign up to set email alerts
|

What Factors Are Associated with Patient-reported Outcome Measure Questionnaire Completion for an Electronic Shoulder Arthroplasty Registry?

Abstract: Background There has been an increase in the use of electronic systems to collect patient-reported outcome measures. There is limited data on the added value of electronic reporting on increasing patient response proportions and little knowledge of which patients are more likely to respond. Questions/purposes (1) What proportion of patients completed patient-reported outcome questionnaires at baseline and at 1 year and 2 years of follow-up after shoulde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…One study of an electronic shoulder arthroplasty registry even described subpopulations that were more or less likely to complete PROMs at different follow-up intervals. 19 Only one-third of our cohort completed assigned PROMs at all follow-up time points, and we did not identify any trends in patient noncompliance over time.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…One study of an electronic shoulder arthroplasty registry even described subpopulations that were more or less likely to complete PROMs at different follow-up intervals. 19 Only one-third of our cohort completed assigned PROMs at all follow-up time points, and we did not identify any trends in patient noncompliance over time.…”
Section: Discussionmentioning
confidence: 73%
“…The most cited demographics for PROM noncompletion following elective orthopaedic procedures are male sex, younger age, and non-White race. 5 , 14 , 16 , 17 , 18 , 19 Although these are commonly cited, a recent study analyzing 9 factors concluded no single patient characteristic can accurately predict loss to follow-up. 20 This study failed to replicate the results of previous orthopaedic studies; however, one publication specific to shoulder arthroscopy did not find differences in PROM compliance, according to patient age or gender.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study, the differences between responders and non-responders in both these studies were small. A study of shoulder arthroplasty patients, however, showed that female patients were less likely to respond [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of PROMs to target surveillance would require robust systems to facilitate PROM data collection. Ling et al 25 retrospectively assessed PROM completion for 1907 patients in their tertiary care centre shoulder arthroplasty register following the introduction of an electronic automated system. The proportion of questionnaires completed at baseline, 1 year, and 2 years were 72%, 47% and 33%, respectively.…”
Section: What Format Of Surveillance Can Identify a Failing Implant?mentioning
confidence: 99%